Bullous pemphigoid in a 3-month-old infant: case report and literature review of this dermatosis in childhood - Eugenio Galdino de Mendonça Reis-Filho; Tainah de Almeida Silva; Luiza Helena de Lima Aguirre; Carmelia Matos Santiago Reis (Sociedade Brasileira de Dermatologia, 2013)
Bullous pemphigoid is an autoimmune subepidermal blistering dermatosis that is uncommon in childhood. We report a case of a female infant, 3 months old, which presented clinical and laboratory data for the confirmatory diagnosis of bullous pemphigoid. The authors used immunohistochemical staining for collagen type IV that allowed the differentiation of bullous pemphigoid from other subepidermal bullous diseases. Opportunely we review the clinical, immunological, therapeutic and prognostic features of this pathology in children.